2021
DOI: 10.3389/fnut.2021.700778
|View full text |Cite
|
Sign up to set email alerts
|

Can Millet Consumption Help Manage Hyperlipidemia and Obesity?: A Systematic Review and Meta-Analysis

Abstract: Many health benefits of millets (defined broadly to also include sorghum) have been advocated, including their roles in managing and preventing diabetes; however, the effects of millets on hyperlipidemia (high lipid levels) have been underrecognized. A systematic review and meta-analysis were conducted to collate available evidence of the impacts of millets consumption on lipid profile, namely total cholesterol (TC), triacylglycerol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 35 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Finger millet is grown mainly for its grain, which is utilized to make traditional food and drinks, while the stalks are used for livestock feed, construction and fuel. Finger millet has various human health benefits such as reducing diabetes [5], obesity [6], osteoporosis [7,8], anemia [6], malaria [9,10] and diarrhea [9,10]. The health values of finger millet are linked to its high calcium, iron and dietary fiber content and being gluten-free.…”
Section: Introductionmentioning
confidence: 99%
“…Finger millet is grown mainly for its grain, which is utilized to make traditional food and drinks, while the stalks are used for livestock feed, construction and fuel. Finger millet has various human health benefits such as reducing diabetes [5], obesity [6], osteoporosis [7,8], anemia [6], malaria [9,10] and diarrhea [9,10]. The health values of finger millet are linked to its high calcium, iron and dietary fiber content and being gluten-free.…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review and meta-analysis of 19 studies shows that long-term consumption of millets can reduce cholesterol, triglyceride, low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), high-density lipoprotein cholesterol (HDL-C), body mass index (BMI), and hypertension, which is another piece of evidence of its potential in reducing the risk of developing cardiovascular diseases (Anitha et al, 2021b). Their richness in iron also helps in improving hemoglobin levels and iron status of the body (Anitha et al, 2021c).…”
Section: Frequency Of Consumptionmentioning
confidence: 99%
“…The findings of this review paper provide scientific evidence supporting diversification of standard diets for children using millets as a solution to malnutrition. Furthermore, millets are a basket of a wide range of nutrients and have been scientifically shown to contribute to serving many of the significant nutrition and health needs globally [ 12 , 13 , 14 , 15 ], not only by tackling child undernutrition, but also by managing type 2 diabetes [ 12 ], lowering total cholesterol levels, obesity [ 13 ], and iron deficiency anaemia [ 14 ]. To bring this solution to reality, awareness about the nutritional value is needed to drive demand and investments in millets along the value chain, from fork to farm.…”
Section: Discussionmentioning
confidence: 99%
“…The year 2023 has been approved by the United Nations as the International Year of Millets, which is expected to attract major attention to millets. Previous systematic reviews and meta-analyses conducted on millets’ health and nutritional benefits showed that regular consumption of millets could help manage the risk of developing type 2 diabetes [ 12 ], reduce hyperlipidaemia, hypertension, and body mass index (BMI), thereby helping manage cardiovascular disease risk [ 13 ], improve haemoglobin level, and reduce anaemia [ 14 ], as well as helping calcium retention [ 15 ]. However, scientific evidence of millets’ role in addressing global crises, such as impaired growth, has had fewer studies undertaken in order to prioritize these crops in nutritional interventions.…”
Section: Introductionmentioning
confidence: 99%